Design and simulation of a novel dual current mirror based CMOS‐MEMS integrated pressure sensor. Issue 3 (3rd February 2021) - Kumar, Shashi; Ropmay, Gaddiella Diengdoh; Rathore, Pradeep Kumar; Rangababu, Peesapati; Akhtar, Jamil
Abstract: This paper presents a novel dual current mirror based CMOS circuit for design and development of highly sensitive CMOS‐MEMS integrated pressure sensors. The proposed pressure sensing structure has been designed using piezoresistive effect in MOSFETs and 5 μm standard CMOS technology parameters. The proposed structure includes six p‐ and n‐channel MOSFETs and two square silicon diaphragms. MOSFETs MP1 and MN1 are the reference transistors and are placed on the substrate. The pressure sensing MOSFETs MP2 and MP3 are integrated at the mid of fixed edge and at the centre of the diaphragm‐1 to sense the maximum tensile and compressive stress developed due to applied pressure. Similarly, the pressure sensing MOSFETs MN2 and MN3 are embedded at the mid of fixed edge and at the centre of the diaphragm‐2. COMSOL Multiphysics and LTspice softwares are used for the design and simulation of proposed sensor. The sensitivity of proposed sensor is found to be approximately 7.7 mV/kPa for an input pressure ranging from 0–200 kPa. The output voltage of the sensor has a temperature sensitivity of approximately −0.2 mV/°C for an operating temperature ranging from −50 to 100 °C at 200 kPa. This CMOS circuit may be an alternative to traditional Wheatstone bridge circuits in future.